Assessement of genotoxicity of Dichlorvos to Mystus vittatus (Bloch) by comet assay - Devesh, Shukla; Nagpure, N S; Ravindra, Kumar; Poonam J, Singh (Indian Journal of Fisheries, 2016)
In the present study, the genotoxicity of dichlorvos, a widely used organophosphate pesticide, was assessed in theair-breathing teleost fish Mystus vittatus using comet assay. The specimens were exposed to sublethal concentrations ofpesticide, viz., 0.045 and 0.022 ppm for a period of one week and the blood samples were collected at 24 h intervals forassessment of DNA damage in terms of Olive tail moment in the erythrocytes. Significant (p